Upaya Peningkatan Hasil Belajar Siswa Melalui Metode Snowball Throwing di Kelas VII SMPS Mamiyai Al-Itihadiyah - Arlina Arlina; Muhammad Syah Bagus; Asmadi Limbong; Rini Nurwana Saragih; Miftahul Jannah Ira; Nur Awaliyah Afrinda Sari (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to improve PAI learning outcomes on the theme of Sincerity, Patience and Forgiving by using the snowball throwing method in class VII of Mamiyai Al-Itihadiyah Private Junior High School Medan. This type of research is Classroom Action Research. The subjects of this study were grade VII students at Mamiyai Al-Itihadiyah Private Junior High School in Medan, totaling 21 students. The data collection techniques used are tests of student learning outcomes, student observation, and teacher observation. The pre-cycle results of students who achieved standard scores were 1 student and those who had not reached standard scores were 20 students with a grade point average of 41%. The learning outcomes of students who achieved standard scores in the first cycle were 10 students and those who had not reached standard scores were 11 students with a total presenatse score of 79%. The learning outcomes of students who achieved standard scores in cycle II were 15 students and those who had not reached standard scores were 6 students with a total presenatse score of 81%. These results prove that the use of the snowball throwing method can improve the learning outcomes of PAI class VII on the theme of Sincerity, Patience and Forgiving at Mamiyai Al-Itihadiyah Private Junior High School in Medan City.